1999
DOI: 10.1159/000012317
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cosmetic Disfigurement to the Severity of Posttraumatic Stress Disorder in Burn Injury or Digital Amputation

Abstract: Background: The purpose of this study was to examine the relationships of physical factors including physical functioning and cosmesis to posttraumatic stress disorder (PTSD) symptoms in patients with burn injury and in patients with digital amputation. Methods: Subjects were 56 patients with burn injury and 26 patients with digital amputation. In addition to assessments of physical factors, psychiatric interviews were administered to examine mental disorders including PTSD and major depression. Results: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
58
2
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 5 publications
(5 reference statements)
10
58
2
2
Order By: Relevance
“…It has been posited that cognitive schema associated with the value placed on appearance (appearance salience), and the perception of attractiveness (appearance valence) play a pivotal role in adjusting to disfigurement in a similar fashion to as played in PTSD (Cash, 202;Cash, 2011;Moss et al, 2014;Thompson, 2012). However, despite clinicians reporting an anecdotal relationship between distress associated with disfigurement and PTSD symptomatology, there are only a small number of studies that have begun to investigate this (Bryant, 1996;Fukunishi, 1999;Roberts, Difede, & Yurt, 2001;Shepherd, 2015). Fukunishi (1999) examined the relationship between the visibility of scars and PTSD symptoms in 56 participants and found that regardless of the size of the scar, females with facial scarring experienced the highest levels of symptoms of trauma-related avoidance and emotional numbing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been posited that cognitive schema associated with the value placed on appearance (appearance salience), and the perception of attractiveness (appearance valence) play a pivotal role in adjusting to disfigurement in a similar fashion to as played in PTSD (Cash, 202;Cash, 2011;Moss et al, 2014;Thompson, 2012). However, despite clinicians reporting an anecdotal relationship between distress associated with disfigurement and PTSD symptomatology, there are only a small number of studies that have begun to investigate this (Bryant, 1996;Fukunishi, 1999;Roberts, Difede, & Yurt, 2001;Shepherd, 2015). Fukunishi (1999) examined the relationship between the visibility of scars and PTSD symptoms in 56 participants and found that regardless of the size of the scar, females with facial scarring experienced the highest levels of symptoms of trauma-related avoidance and emotional numbing.…”
mentioning
confidence: 99%
“…However, despite clinicians reporting an anecdotal relationship between distress associated with disfigurement and PTSD symptomatology, there are only a small number of studies that have begun to investigate this (Bryant, 1996;Fukunishi, 1999;Roberts, Difede, & Yurt, 2001;Shepherd, 2015). Fukunishi (1999) examined the relationship between the visibility of scars and PTSD symptoms in 56 participants and found that regardless of the size of the scar, females with facial scarring experienced the highest levels of symptoms of trauma-related avoidance and emotional numbing. This suggests that gender may be important in PTSD symptomatology associated with scarring.…”
mentioning
confidence: 99%
“…Estes pacientes sofrem com intromissão não desejada tais como olhares fixos ou comentários (7)(8)(9) . O efeito psicossocial negativo destas reações nos pacientes já foi demonstrado em diferentes grupos de pacientes, por exemplo, em pacientes com anormalidades congêni-tas, queimaduras faciais, manchas vinho do porto ou câncer em regiões de cabeça e pescoço (6)(7)(10)(11) . A pressão da sociedade para corresponder com uma aparência idealizada é a raiz da angústia dos pacientes.…”
unclassified
“…Indian Review Article by PK DALAL, RAHUL SAHA, et al; states Stress disorders and depression are prevalent. For example, acute stress disorder (ASD) has been reported in 18-26% in Greek, [31] US, [32] and Dutch [33] samples.…”
Section: Psychiatric Manifestation In Post Burn Patientsmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) has been observed in one-third of Japanese [34] and US [35] samples between 3 and 6 months postburn, and in 15-20% of Dutch [33] and Greek [31] samples at 1 year. PTSD was more common among veterans with extensive burns than among those with spinal injuries, amputations, major chest trauma, heart failure, or cardiac arrest.…”
Section: Psychiatric Manifestation In Post Burn Patientsmentioning
confidence: 99%